2014
DOI: 10.1177/0004563214521399
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate homeostasis and disorders

Abstract: Recent studies of inherited disorders of phosphate metabolism have shed new light on the understanding of phosphate metabolism. Phosphate has important functions in the body and several mechanisms have evolved to regulate phosphate balance including vitamin D, parathyroid hormone and phosphatonins such as fibroblast growth factor-23 (FGF23). Disorders of phosphate homeostasis leading to hypo-and hyperphosphataemia are common and have clinical and biochemical consequences. Notably, recent studies have linked hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
146
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(149 citation statements)
references
References 250 publications
(257 reference statements)
1
146
1
1
Order By: Relevance
“…Several cross-sectional studies have found a low tion, at both the baseline and the follow-up visits (1.5% and 3.1%, respectively), we are confident that our results were negligibly influenced by our failure to measure the serum 25OHD levels at the follow-up visit. Moreover, serum phosphorus levels were not measured, although hyperphosphoremia appears to be an independent risk factor for CVD 32) . We also did not assess ABI in other ways (e.g., toe pressure versus ankle pressure) in diabetic participants or patients with diseases at high risk of vascular calcifications 18) .…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies have found a low tion, at both the baseline and the follow-up visits (1.5% and 3.1%, respectively), we are confident that our results were negligibly influenced by our failure to measure the serum 25OHD levels at the follow-up visit. Moreover, serum phosphorus levels were not measured, although hyperphosphoremia appears to be an independent risk factor for CVD 32) . We also did not assess ABI in other ways (e.g., toe pressure versus ankle pressure) in diabetic participants or patients with diseases at high risk of vascular calcifications 18) .…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal serum phosphate levels are a common finding in seriously ill patients, and hypophosphatemia (usually defined as serum phosphate < 0.8 mmol/L) is commonly seen in patients with severe infections [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate is essential to the biology of life, as the fundamental energy currency of cells in adenosine triphosphate (ATP), as a critical component of nucleic acids, as a molecular switch controlling protein function, as a component of membrane phospholipids, and as a buffer to changes in pH [13]. Most phosphorous in the human body is stored in bones and teeth, and the rest is predominantly intracellular, where concentrations are 100 times greater than in plasma [9,13]. Only about 1% of body phosphorous content is contained in the plasma, but this phosphate is important because it is the medium of exchange between different body compartments, particularly when phosphate is required rapidly [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 80-85% of phosphate is present in the skeleton, 10-15% in soft tissues, and only <1% of phosphate circulates in the serum of a healthy adult [1]. Although the required phosphate level is about 580 mg/day, some individuals' daily phosphorus intake exceeds the upper tolerable limit (4,000 mg/day) [2].…”
Section: Introductionmentioning
confidence: 99%